2016
DOI: 10.1159/000447495
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Patient Characteristics among Men Choosing Open or Robot-Assisted Radical Prostatectomy in Contemporary Practice - Analysis of Surveillance, Epidemiology, and End Results Database

Abstract: Objective: To examine characteristics of robot-assisted (RARP) and open radical prostatectomy (ORP) patients. Patients and Methods: We relied on the Surveillance, Epidemiology, and End Results-Medicare-linked database and focused on prostate cancer patients between 2008 and 2009. In multivariable logistic regression analyses, we predicted RARP. Results: Of 5,915 patients, 3,476 (58.8%) underwent RARP and 2,439 (41.2%) ORP. Patients within intermediate (OR 1.4, p = 0.01) or highest (OR 1.5, p = 0.02) education … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…The data from Canada also showed that laparoscopic radical prostatectomy (LRP) and robot-assisted radical prostatectomy (RARP) were more likely to be performed at academic and high-volume centres compared to open radical prostatectomy (ORP). This has also been shown by Schiffmann et al [14] who not only described that patients treated by high-volume surgeons were more likely to undergo RARP rather than ORP but also showed that patients residing in rural areas and those with cT2 and higher were less likely to undergo RARP compared to ORP. Furthermore, another study from Japan showed that there is an increased risk for complications in RARP associated with hospital and surgeon volume [15].…”
Section: Discussionsupporting
confidence: 71%
“…The data from Canada also showed that laparoscopic radical prostatectomy (LRP) and robot-assisted radical prostatectomy (RARP) were more likely to be performed at academic and high-volume centres compared to open radical prostatectomy (ORP). This has also been shown by Schiffmann et al [14] who not only described that patients treated by high-volume surgeons were more likely to undergo RARP rather than ORP but also showed that patients residing in rural areas and those with cT2 and higher were less likely to undergo RARP compared to ORP. Furthermore, another study from Japan showed that there is an increased risk for complications in RARP associated with hospital and surgeon volume [15].…”
Section: Discussionsupporting
confidence: 71%
“…Marketing campaigns, hospital and urologist competition, and centralised health systems may have also contributed to the perception that RARP is superior [ 9 , 10 ]. Furthermore, patient and surgeon characteristics may differ significantly between ORP and RARP cohorts [ 11 ]. Due to conflicting evidence and its increasing adoption [ 12 ], ongoing comparison of outcomes is warranted that is focussed on issues that impact quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Radical prostatectomy (RP) represents one of the most frequently used treatment options in localised prostate cancer, usually performed as either retropubic open RP (ORP) or robot‐assisted RP (RARP). Since its introduction almost 20 years ago, RARP has evolved into the predominant surgical approach in many industrialised countries , leading to the favourable development of centralisation and creation of high‐volume centres . However, reliable data on comparisons of the two surgical approaches are scarce.…”
Section: Introductionmentioning
confidence: 99%